Automation - blessing or curse, 1956 (London, 1956)
1956 1951-1960 "Automation - blessing or curse, 1956" [BW0170], 1956, Trades Union Congress This pamphlet by Bob Edwards MP and published by the London Cooperative Society Political Committee details warns that the increasing use of automation in industry may lead to greater unemployment.